Review on solar disturbance studies and electric power transmission line fault in Malaysia - Mohammad Zakaria Mohd Alias; Mariyam Jamilah Homam; Faridah Hanim Mohd Noh (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
This work is a review on previous research and studies on the solar disturbance activities and faults that occur on the electric power transmission line. Research has shown that low latitude regions could also be affected by solar disturbance events. The effects of these events on earth are considerable and may cause electric power transmission failure. Geomagnetically induced current is one of the ground impacts to the transmission line, which may cause fault or disturbance and consequently power system failure. Solar disturbance data from magnetometers and electric power transmission line fault data from a digital fault recorder are reviewed in this work. These data would be valuable in determining the characteristics and effects of solar disturbances on Malaysia’s electric power transmission lines.